If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4 + -5 = 3x + 1 Reorder the terms: 4 + -5 + 2x = 3x + 1 Combine like terms: 4 + -5 = -1 -1 + 2x = 3x + 1 Reorder the terms: -1 + 2x = 1 + 3x Solving -1 + 2x = 1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -1 + 2x + -3x = 1 + 3x + -3x Combine like terms: 2x + -3x = -1x -1 + -1x = 1 + 3x + -3x Combine like terms: 3x + -3x = 0 -1 + -1x = 1 + 0 -1 + -1x = 1 Add '1' to each side of the equation. -1 + 1 + -1x = 1 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 1 + 1 -1x = 1 + 1 Combine like terms: 1 + 1 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| 5[8+(81)]= | | f+12=4 | | f+12=-4 | | 6x-3(7-2x)=14 | | 5-7.12-15= | | (9(m+5)-15)+(2(m-3)+4)= | | 6(7au)+u=36+u | | 3x-3(5-2x)=3 | | 8a^3+27b^3+64c^3=72abc | | 9(2X-1)=3(3x+3) | | 1p+2=-1 | | 3(2x+3)=2(3x+1) | | 2a^2-5a-4=0 | | 3u^2+12u+6=0 | | x(x-4)(x+11)=0 | | 4d*-3d= | | (28-4i)-(10-30)=0 | | 3+8x=14-3x | | 1-4(100+36s)=15-4s | | y^2-4y=8 | | 8x+8-ax-a=0 | | 3(x-3)=2(x-2)-(5-3x) | | 0.50(8n-2)=16-30n | | 2x^2+10x-80=0 | | x(2x+3)(x-4)=6 | | x(2x+5)(x-4)=6 | | 9m+5-4m=-20 | | 13x-30=7x-14 | | -6(x-3)=-3(x+9) | | (x-p)(x^2+11x+15)=(x^2-9)(2x+q) | | 2x^2-3-15=0 | | k+84738398=98393398 |